Wnt signaling directs a metabolic program of glycolysis and angiogenesis in colon cancer. (13th May 2014) - Pate, Kira T; Stringari, Chiara; Sprowl‐Tanio, Stephanie; Wang, Kehui; TeSlaa, Tara; Hoverter, Nate P; McQuade, Miriam M; Garner, Chad; Digman, Michelle A; Teitell, Michael A; Edwards, Robert A; Gratton, Enrico; et al.
Abstract Much of the mechanism by which Wnt signaling drives proliferation during oncogenesis is attributed to its regulation of the cell cycle. Here, we show how Wnt/β‐catenin signaling directs another hallmark of tumorigenesis, namely Warburg metabolism. Using biochemical assays and fluorescence lifetime imaging microscopy (FLIM) to probe metabolism in vitro and in living tumors, we observe that interference with Wnt signaling in colon cancer cells reduces glycolytic metabolism and results in small, poorly perfused tumors. We identify pyruvate dehydrogenase kinase 1 (PDK1) as an important direct target within a larger gene program for metabolism. PDK1 inhibits pyruvate flux to mitochondrial respiration and a rescue of its expression in Wnt‐inhibited cancer cells rescues glycolysis as well as vessel growth in the tumor microenvironment. Thus, we identify an important mechanism by which Wnt‐driven Warburg metabolism directs the use of glucose for cancer cell proliferation and links it to vessel delivery of oxygen and nutrients.